Misi Lintas Budaya dalam Perspektif Perjanjian Lama - Hinadaka, Jon Jusuf (Sekolah Tinggi Teologi Borneo, 2021)
Abstract: After His resurrection and before He taken up into heaven, Jesus gave a command which knowen as The Great Commission in Matthew 28:18, to His disciples to go, make disciples of all nations, biptizing them, and teaching them to obay everything Jesus has commanded. That command also an order to the believer in this time and to the future as Jesus witness. Therefore, Christian Mission is not just focusing in the Gospel Matthew 28:18-20 only. But it is focusing to all Bible, sometimes implicitly and explicitly with one central theme as Jessus Christ which is the core from the news itself. Without Bible, the evangelism to the whole world not just imposible but it cannot be imagined. The Bible gives us a responsibility to world evangelization, gives us Gosple to spread it, gives us the way how to spread it, and promeses us that Gosple as the power of God to save every one who believe in it. Even, the fact of history, in the past time and this time, show us that the level of church commitment for world evangelization match with the level of conviction to the Bible. If Christian has lost the hope to the Bible, they are not determined to do world evangelizatio.Keywords: covenant; protoevangelium; sinAbstrak: Setelah kebangkitan-Nya sebelum Ia naik ke surga, Yesus memberikan perintah yang dikenal sebagai Amanat Agung dalam Matius 28:18-20, kepada murid-murid-Nya untuk pergi, menjadikan semua bangsa murid-Nya, membaptis, dan mengajarkan mereka untuk melakukan segala sesuatu yang Yesus perintahkan. Perintah ini juga merupakan mandat bagi orang percaya masa kini maupun di masa yang akan datang sebagai saksi-saksi Kristus. Namun, Misi Kristen bukan hanya bertitik tolak pada Injil Matius 28:18-20 saja. Tetapi dari keseluruhan Alkitab, terkandung secara implisit maupun eksplisit satu tema sentral yaitu Yesus Krsitus yang merupakan isi atau inti dari berita itu sendiri. Tanpa Alkitab penginjilan dunia bukan saja tidak mungkin tapi sungguh tidak dapat dibayangkan. Alkitab memberikan kita tanggung jawab untuk menginjili dunia, memberi kita Injil untuk diberitakan, memberitahukan kita bagaimana memberitakannya, dan menjanjikan bahwa Injil adalah kekuatan Allah untuk keselamatan setiap orang percaya. Bahkan fakta sejarah, baik pada masa lalu maupun masa kini, memperlihatkan bahwa tingkat komitmen gereja terhadap penginjilan dunia sepadan dengan tingkat keyakinannya terhadap otoritas Alkitab. Bila orang Kristen kehilangan keyakinannya pada Alkitab, mereka tidak berketetapan hati untuk melakukan penginjilan.Kata kunci: dosa; perjanjian; proto evangelium